Evaluasi Pelaksanaan Program Bantuan Stimulan Perumahan Swadaya (BSPS) dalam Peningkatan Kualitas Hunian Masyarakat Berpenghasilan Rendah (MBR) di Nagari Sirukam, Kabupaten Solok - Qalbi, Angel Halsya Dwi; Adnan, M. Fachri (Lembaga Yasin AlSys, 2025)
Bantuan Stimulan Perumahan Swadaya (BSPS) program is a government initiative aimed at improving housing quality for low-income communities through self-help-based assistance. However, its effectiveness at the local level often faces challenges such as targeting inaccuracies and administrative limitations. This study seeks to evaluate the implementation of the BSPS program in Nagari Sirukam, Solok Regency, using William N. Dunn’s policy evaluation framework and the evaluation standards of Mahesh Patel and Craig Russon, which include four aspects: utility, feasibility, propriety, and accuracy. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. Informants were selected purposively and included program beneficiaries, village government officials, and Field Facilitators (TFL). The findings indicate that the implementation of the BSPS program in Nagari Sirukam has been moderately successful, particularly in terms of transparency, community participation, and alignment with local cultural values such as gotong royong. However, challenges remain in targeting accuracy and administrative capacity, resulting in some low-income households not being accommodated as beneficiaries. These findings highlight the need for improvements in data accuracy, implementation oversight, and policy flexibility to ensure that the BSPS program becomes more targeted, inclusive, and socially equitable.